Antimicrobial assay of shigatoxigenic E. coli (STEC) and enteropathogenic E. coli (EPEC) isolated from diarrhoeic faecal samples of piglets and infants in Mizoram - BEGUM, JUBEDA; DUTTA, TAPAN KUMAR; CHOUDHARY, PARIMAL ROY; CHANDRA, RAJESH; VARTE, ZOMUANKIMA (The Indian Journal of Animal Sciences, 2015)
Antimicrobial resistance is a common problem which is accelerating day by day in veterinary medicine. The main reason is believed to be the indiscriminate and irrational use of antibiotics. Diarrhoeic faecal samples (584: 320 from piglets and 264 from infants) were collected from different farms and hospitals located in different districts of Mizoram. Out of 1,260 E. coli isolates, 65 (5.15%) E. coli isolates were found positive for at least 1 virulence gene (stx1, stx2, eaeA, hlyA) under the study, of which 40 (3.17%) and 25 (1.98%) were recorded as STEC and EPEC, respectively, when screened by multiplex PCR. All the 65 E. coli isolates were subjected to antimicrobial sensitivity test against 12 commonly used antimicrobial agents. Among the isolates from piglets, highest sensitivity was exhibited by chloramphenicol (89.58%) and highest resistance by nalidixic acid (85.41%). On the other hand, enrofloxacin exhibited 100% sensitivity while amoxicillin, polymyxin B and kanamycin exhibited 100% resistance among the infant isolates. It may be concluded that 5.15% isolates were positive for virulence and the isolates showed increased tendency of resistance to many of the commonly used antibiotics reflecting a greater threat to treat the commonly occurring diseases with antibiotics.